Spiking neural network equalization on neuromorphic hardware for IM/DD optical communication - Arnold, Elias; Böcherer, Georg; Müller, Eric; Spilger, Philipp; Schemmel, Johannes; Calabrò, Stefano; Kuschnerov, Maxim (Arxiv, 2022)
A spiking neural network (SNN) non-linear equalizer model is implemented on the mixed-signal neuromorphic hardware system BrainScaleS-2 and evaluated for an IM/DD link. The BER 2e-3 is achieved with a hardware penalty less than 1 dB, outperforming numeric linear equalization.